2006
DOI: 10.1103/physreve.73.061701
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental optical studies of cholesteric liquid crystal films with thermally induced pitch gradients

Abstract: The reflection properties of cholesteric films with thermally induced pitch gradients are theoretically and experimentally studied. It is shown that the optical behavior of such films corresponds to the averaged contribution of a number of stochastic pitch variation profiles, due to the transversal and longitudinal nonuniformities that develop in the helical structure of such samples. Depending on the annealing time, both narrow-band and broadband behavior can be selectively achieved. The influence of the pitc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 31 publications
0
38
0
1
Order By: Relevance
“…2, which in turn leads to shorter wavelengths inside the dielectric medium. Next, we study light transmission through a CLC thin film [43,44] placed between two glass slides of refractive index n g 1.5, where the nematic host material is E7. The thickness of the slab is equal to d 10P 0 , where P 0 450 nm is the cholesteric helical pitch.…”
Section: In This Section the Accuracy Of The Proposed Fdtd Scheme Ismentioning
confidence: 99%
“…2, which in turn leads to shorter wavelengths inside the dielectric medium. Next, we study light transmission through a CLC thin film [43,44] placed between two glass slides of refractive index n g 1.5, where the nematic host material is E7. The thickness of the slab is equal to d 10P 0 , where P 0 450 nm is the cholesteric helical pitch.…”
Section: In This Section the Accuracy Of The Proposed Fdtd Scheme Ismentioning
confidence: 99%
“…This unique property has provided the possibility of designing tunable mirrorless laser devices that explore the pitch sensitivity to external agents, such as an electric field ͓23͔, temperature ͓24͔ and concentration ͓25͔ gradients, and uv irradiation ͓26-28͔. The above feature has been explored to develop broadband reflectors based on cholesteric systems with a continuous pitch gradient ͓18,19,25,29,30͔. Further,it was demonstrated that the introduction of defects in the helical structure induces the emergence of resonance modes inside the photonic stop band ͓12,16,31-33͔.…”
Section: Introductionmentioning
confidence: 99%
“…To prepare cholesteric films with broadband reflection properties, many studies have been done to broaden the reflection bandwidth . Forming a pitch gradient or nonuniform pitch distribution is an important mechanism for broadening the reflection band.…”
Section: Introductionmentioning
confidence: 99%
“…The different polymerization rates of bifunctional polymerizable cholesteric monomer and monofunctional polymerizable nematic monomer lead to molecular diffusion. Michel Mitov et al stacked a cholesteric phase polysiloxane liquid crystal polymer film reflecting red light and another film reflecting blue light . Heat treatment was carried out to cause thermal diffusion between molecules, and the film was rapidly cooled to the temperature below the glass transition to fix the gradient of pitch.…”
Section: Introductionmentioning
confidence: 99%